PENGARUH PENDAPATAN KOPERASI TERHADAP KESEJAHTERAAN ANGGOTA (STUDI KASUS KOPERASI POLISI DAERAH KALIMANTAN BARAT DI PONTIANAK) - Priska, Mariana; Aminuyati, Aminuyati; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is titled "The Effect of Cooperative Revenues on Members' Welfare. (Case Study in the West Kalimantan Regional Police Cooperative in Pontianak). The research method used is a quantitative descriptive method. Data collection techniques used are indirect communication techniques and documentary study techniques. The data collection tool uses interview guidelines, questionnaires and data.  The results of this study are as follows: 1) based on the results of a simple regression analysis between Cooperative Income items (variable X) as a whole to Member Welfare (variable Y) shows that Cooperative Income has a positive influence. 2) From the results of hypothesis testing, it is shown by the results of the calculation of the F test that shows the value of 144,882 with a probability level of 0,000 which is far below the alpha of 5%. That means that together the independent variable Cooperative Income affects Welfare. 3) The results of the analysis of the influence of items Cooperative Revenue (variable X) as a whole to the Members' Welfare (variable Y) shows that Cooperative Revenue has a positive influence, so it is usually said to have an influence, or Cooperative Income (variable X) has an effect on the Welfare (variable Y) member of the West Kalimantan Regional Police Cooperative (POLDA), namely the effect of Pearson. 787. This means that the influence between Cooperative Income (variable X) as a whole to Welfare (variable Y) is 0.787 (the relationship between the two variables is quite strong).  Keywords: Income, Welfare of Cooperative members